Pemilihan Hotel Terbaik Berdasarkan Review Pengguna Menggunakan Metode Operational Competitiveness Rating Analysis (OCRA) - Fadila Shely Amalia (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2024)
Choosing the best hotel based on user reviews is an important step for modern travelers who rely on the experience and feedback of others before making a decision. The purpose of this study is to provide recommendations for users in the selection of hotels based on reviews from other users by applying the OCRA method in ranking the best hotel alternatives. The ranking results using the OCRA method based on the results of hotel user reviews on the TripAdvisor application were obtained for rank 1 with a value of 1.7635 obtained under the name Novotel Lampung Hotel, rank 2 with a value of 0.6149 obtained under the name Radisson Lampung Kedaton, and rank 3 with a value of 0.4268 obtained under the name BATIQA Hotel Lampung.